PHENOMENOLOGY OF CULTURE SHOCK AMONG EXPATRIATE TEACHERS IN SEMARANG - Dhia Qomara Rizani; Intan Ratnawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
IndoneIndonesia is a country that is a destination for expatriates from all over the world. Expatriates come to Indonesia for various matters, both business and to work for organizations and institutions in Indonesia. However, there are still few studies that examine how expatriates from various countries in the world can adapt to the culture and society in Indonesia. There are 8 school foundations in Semarang that work together with Foreign Education Institutions (LPA), as a result this school will bring in teachers to teach in Semarang schools which are affiliated with several countries in the world. Understanding how expatriate teachers can easily adapt to Indonesian culture is very important. By accelerating the adaptation process, expatriate teachers can show more optimal teaching performance quickly and precisely. For this reason, this research will conduct studies in international-based schools where the teachers are imported directly from abroad or the teachers are expatriates. This study uses the culture shock variable to analyze expatriate teachers in Semarang.